The Master and the Masks: Literary Motifs (Confluenţe Bibliologice, 2025)
The reason for the appearance of this article is based, on the one hand, the celebration of the 250th anniversary of the play-tale „The Stag King“ (1762) of Italian playwright Carlo Gozzi, and on the other hand – the fairy tale „Lady in blue at the end of the day” by Anne-Lou Steininger published in „Foreign Literature Studies” journal in 2013. The author tells us about philosophical/ literary ideas and the use of mask and characters in literature.
Keywords: Steininger Anne-Lou (1963); Gozzi Carlo (1720 – 1806)